2014
DOI: 10.1287/mnsc.2014.1967
|View full text |Cite
|
Sign up to set email alerts
|

Seeing Stars: Matthew Effects and Status Bias in Major League Baseball Umpiring

Abstract: This paper tests the assumption that evaluators are biased to positively evaluate high status individuals, irrespective of quality. Using unique data from Major League Baseball umpires' evaluation of pitch quality, which allow us to observe the difference in a pitch's objective quality and in its perceived quality as judged by the umpire, we show that umpires are more likely to over-recognize quality by expanding the strike zone, and less likely to under-recognize quality by missing pitches in the strike zone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
105
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(117 citation statements)
references
References 56 publications
0
105
0
Order By: Relevance
“…The third category of bias is reputation, occurring in two ways. Using the same criteria, the evaluation of pitches in baseball, Kim and King (2014) found that umpires are likely to overestimate the quality of pitches of high-status athletes, for example players voted into the All Star game. In addition, this effect is moderated by properties that are attributed to the pitching style of the respective pitchers.…”
Section: Introductionmentioning
confidence: 99%
“…The third category of bias is reputation, occurring in two ways. Using the same criteria, the evaluation of pitches in baseball, Kim and King (2014) found that umpires are likely to overestimate the quality of pitches of high-status athletes, for example players voted into the All Star game. In addition, this effect is moderated by properties that are attributed to the pitching style of the respective pitchers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Stern, Dukerich, and Zajac () showed that an emerging firm's likelihood of forming an alliance with an incumbent increases when the research achievements of its founding scientist (i.e., publications and citations) are congruent with the prestige of the university from which he or she graduated. Similarly, Kim and King () found that the level of congruity between two quality signals: a pitcher's number of All‐Star appearances and his career average of walks per batters faced positively relate to the evaluation of his pitch quality by Major League Baseball umpires.…”
Section: Theory and Hypothesesmentioning
confidence: 96%
“…1 Recent work has applied these insights to ex post evaluation. For example, Kim and King (2014) demonstrate that high status baseball players are more likely to benefit from judgment calls made by umpires, nicely illustrating how quality can be inferred even when not precisely observed. Waguespack and Sorenson (2011) find that, holding film content constant, rating boards are more likely to deem movies from high status studios appropriate for younger audiences.…”
Section: Persistence In Performance and Subjective Cumulative Advantagementioning
confidence: 97%
“…For example, in a sporting event, a well-defined outcome might have taken place but the evaluator has difficulty properly observing it, as with judgment calls among sporting referees. This notion of subjective error underpins calls for the use of instant replay in sports (Kim and King 2014).…”
Section: Persistence In Performance and Subjective Cumulative Advantagementioning
confidence: 99%